DIET OF EUROPEAN GRAYLING (THYMALLUS THYMALLUS L.) FROM RIVERS OF THE ZAKARPATTYA IN CURRENT CONDITIONS - A. Khandozhivska; S. Krazhan; A. Mruk; S. Koba (Ribogospodarsʹka Nauka Ukraïni, 2014)
Purpose. Determination of the diet spectrum of European grayling (Thymallus thymallus), qualitative and quantitative composition of the gut content of age groups (2+, 1+, 0+) from Teresva and Tereblya Rivers of the Zakarpattia region.